Current trends in miRNAs and their relationship with oral squamous cell carcinoma - Pérez-Sayáns, Mario; Pilar, Gayoso-Diz; Barros-Angueira, Francisco; Suárez-Peñaranda, José Manuel; Fernández, Alexia Conde; Gándara-Rey, José Manuel; García-García, Abel (Journal of oral pathology & medicine, 2012)
J Oral Pathol Med (2012) 41: 433–443 A micro RNA (miRNA) is a single‐stranded endogenous, non‐coding RNA, with length ranging between 18 and 24 nucleotides and the ability of regulating the expression of other genes on a post‐transcriptional level by means of various processes, degradation or repression of target mRNA. miRNAs play a crucial role in regulating fundamental processes such as cell cycle, differentiation and apoptosis; thus, their deregulation can affect normal cell growth and development, and even participate in carcinogenesis. The goals of this paper are: to outline the formation and functions of miRNAs; to determine their role in oral squamous cell carcinoma; to analyze the different miRNAs described and their roles as oncogenes or tumor suppressor genes, depending on their overexpression or subexpression; to describe the different polymorphisms and epigenetic alterations identified; and to determine their role in multidrug resistance.